Estudo sobre reações adversas e complicações de preenchedores cutâneos de ácido hialurônico: uma revisão sistemática - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The skin is the most visible organ of the body, where aging is very noticeable, where it can change the appearance associated with aging or extrinsic, such as the appearance of expression lines, wrinkles, furrows and rhytids, this makes people look for cosmetic procedures to improve the appearance of your skin. Ideal filler (AH) filler inclusions which are usedalur of aging, replacing lost volume is a lost filler, because replacing dermal facial, being in a lot lost. This study is a systematic review being a qualitative description research, with reports of adverse reactions, where cases of reactions and complications arising from the use of HA as a facial filler were studied, with reports of adverse reactions with ischemic adverse reactions and reported from 2003 to 2021. There were 213 cases of unreported adverse reactions with HA filling in different regions of the face, with 75 cases of adverse reactions reported with HA fillings in different regions of the face, with 75 adverse reaction regions with HA filling in different regions of the face. These cases of occurrences can occur with several species, with the total occurrences of HA leading to the occurrence of adverse reactions, the most serious occurrences of diverse occurrences, with the use of more than 75 adverse reactions of occurrences in total. Among the severe cases, some rare cases stood out, such as three cases of alopecia, six of Nicholas Syndrome, two of thrombosis and one of lymphangioma, related to ischemic complications. And three cases of xanthelasma and one of sarcoidosis, the latter related to non-ischemic complications. The filling site with the most adverse reactions reported was the nasolabial fold, followed by lips and nose. Rarer reactions may become more urgent, due to increased filler use or currently. In this way, injection professionals must work to minimize risks by adopting a safer injection technique and having a deep knowledge of facial anatomy. They should also be protocols for presenting complications, having clear and forceful referral routes. Therefore, the results provide a theoretical basis for considering filling a viable facial matching strategy, which can lead to adverse reactions and is not entirely safe.
Keywords: REAÇÃO ISQUÊMICA; REAÇÃO NÃO ISQUÊMICA; COMPLICAÇÕES PREENCHEDORES; REAÇÕES RARAS; REAÇÕES RARAS; ISCHEMIC REACTION; NON-ISCHEMIC REACTION; FILLING COMPLICATIONS; RARE REACTIONS; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA